Análise bibliográfica de mulheres negras em cargos de gestão escolar pública por meio de ações afirmativas - Feitosa, Larissa Natalia (Universidade Federal de São Carlos, 2023)
The objective of the research was to present a selection of studies that analyze the impacts of affirmative action policies with the objective of increasing the presence of black women in spaces of public school management. It is about identifying a measure of analysis of the implication of a public policy, that is, the adoption of affirmative action measures. Thus, the following question arises: how do affirmative action policies impact the presence of black women in school management? To this end, a bibliographical survey and analytical review of studies carried out from this interface in the Brazilian Digital Library of Theses and Dissertations (BDTD) were carried out. The results indicate that the interface of research on black women in school management is still an open field, considering the scarcity of articles found, with only two. We conclude that we still have a lot to progress and advance in the struggle, in order to provide and reach a greater number of black women occupying public management positions.
Bibliographical analysis of black women in public school positions through affirmative actions
Keywords: Ações afirmativas; Gestão escolar; Relações étnico-raciais; Gênero; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO